2003
DOI: 10.1016/s0266-7681(03)00082-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hand Trauma: The Hand Injury Severity Scoring System (HISS) and Subsequent Impairment and Disability

Abstract: This study was designed to evaluate correlations between the hand injury severity scoring system (HISS) and measures of impairment and disability obtained 6 months after a hand injury. A statistically significant positive correlation was found between the severity of the injury (HISS) and residual impairment, as measured with the American Medical Association's (AMA) "Guides to the evaluation of permanent impairment, 4th edition". No statistically significant correlation was found between the severity of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
3
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 10 publications
7
54
3
4
Order By: Relevance
“…The relationship between HISS and the functional outcome after hand fracture surgery has been controversial. Some studies have reported a strong correlation between HISS and patientreported outcomes [12,19], whereas others have not shown any statistically significant correlation [15]. In the current study, HISS was associated with a decrease in QuickDASH scores up to a 6-month followup.…”
Section: Discussioncontrasting
confidence: 54%
“…The relationship between HISS and the functional outcome after hand fracture surgery has been controversial. Some studies have reported a strong correlation between HISS and patientreported outcomes [12,19], whereas others have not shown any statistically significant correlation [15]. In the current study, HISS was associated with a decrease in QuickDASH scores up to a 6-month followup.…”
Section: Discussioncontrasting
confidence: 54%
“…[17,41,48,49] In our material we found a correlation between the DASH score and the HISS (SRCC 0.336, p<0.001, n = 96) and also between the DASH score and HISS grade (SRCC 0.301, p = 0.002, n = 107). Although these correlations were weak, they indicate that the more severe the initial wood splitter injury, the worse the outcome.…”
Section: Dashsupporting
confidence: 58%
“…[30] Mink van der Molen et al found that HISS was correlated to the degree of impairment resulting from hand injury assessed according to the American Medical Association (AMA) guidelines. [20,41] An obvious limitation of the HISS system is that injuries proximal to the CMC joints are not included. This excludes many of the more severe hand injuries which often have a proximal component.…”
Section: Hand Injury Severity Scoring Systemmentioning
confidence: 99%
“…These studies reported more than 50% of injuries to the dominant hand. 1,3 However, Mink and colleagues 10 observed dominant hand injuries in about 37% of their sample. In this study, 12% had a hand injury in combination with other injuries, which was in contrast with another study in which 4% had combined injuries.…”
Section: Discussionmentioning
confidence: 97%